An Account of Iranian Pregnant Women' Experiences of Spousal Role: An Ethnophenomenological Exploration - Fatemeh Erfanian Arghavanian; Abbas Heydari; Mohsen Noghani Dokht Bahmani; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2020)
Background & aim: Women experience many physical and emotional changes during pregnancy. Simultaneously, they experience dramatic alterations in their family structure and function including changes in the spousal role of couple. Due to the scarcity of studies in this regard, the present study aimed to provide an account of women's experiences of spousal role during pregnancy. Methods: In this ethnophenomenological exploration, 25 pregnant women referred to health centers, prenatal clinics of hospitals, and private offices of obstetricians, were included in the study. Participants were selected using purposive sampling with a maximum variation strategy between October 2016 and March 2017. Data were collected using semi-structured in-depth individual interviews, vignette interviews, and participant observations. The data were analyzed adopting Van Manen's descriptive-interpretive phenomenological approach (1997) using MAXQDA software (version 10). Results: The main theme of "attempt to preserve spousal role" was emerged. This theme was derived from four themes of "mother's effort to manage marital issues", "couples' interactions", "husband physical and mental care of wife" and "mother's conflicts with the rights and duties attached to the spousal role". Conclusion: Pregnant women consider the spousal role to be one of their main duties and regarded it as their central responsibility. Therefore, they meticulously play their spousal role to provide constructive interactions with their spouses. The inclusion of gender-sensitive programs and services, including providing prenatal care, is of utmost importance to pregnant women in order to meet their needs to play their spousal role, appropriately.